Do agency costs matter? Evidence from Egypt on the capital structure-performance nexus - El Mahdy, Asmaa Hamdy Abdelaziz Mohamed; Samir, Nour Amr (Research Papers in Economics and Finance, 2025)
This study has two main objectives: (i) to explore the relationship between capital structure (CS) and firm performance (FP) among non-financial firms listed on the Egyptian Exchange (EGX30), and (ii) to analyze how agency costs (AC) influence this relationship as a moderator. The research uses Panel Least Squares (PLS) to examine how AC affects the association between CS and FP. The sample includes 200 firm observations annually from 20 non-financial firms listed on the Egyptian Stock Exchange (EGX30) from 2014 to 2023. The debt-to-equity ratio (D/E) measures CS, while return on equity (ROE) assesses FP. The asset utilization ratio (AUR) gauges AC. Results indicate that CS positively affects FP. Additionally, AC demonstrates a positive moderating effect on the relationship between CS and FP. To the best of the authors’ knowledge, this is the first study to examine the moderating influence of AC on the association between CS and FP in Egypt.